Comparisons of weight changes between sodium‐glucose cotransporter 2 inhibitors treatment and glucagon‐like peptide‐1 analogs treatment in type 2 diabetes patients: A meta‐analysis. Issue 4 (23rd March 2017) - Cai, Xiaoling; Ji, Liwei; Chen, Yifei; Yang, Wenjia; Zhou, Lingli; Han, Xueyao; Zhang, Simin; Ji, Linong
Abstract : A total of 97 RCTs were included in this meta‐analysis, treatment with SGLT2 inhibitors and treatment with GLP‐1 analogs led to comparable weight changes from baseline, which are both with significance when compared with placebo treatment. Abstract: Aims/Introduction: To evaluate the efficacy of weight changes from baseline of the sodium‐glucose cotransporter 2 (SGLT2) inhibitors treatment and glucagon‐like peptide‐1 (GLP‐1) analogs treatment after comparisons with a placebo in type 2 diabetes patients, and the associated factors. Materials and Methods: Studies were searched from when recording began, June 2004, until June 2015, and re‐searched in July 2016, and placebo‐controlled randomized trials in type 2 diabetes patients with a study length of ≥12 weeks were included. Results: A total of 97 randomized controlled trials were included. Compared with a placebo, treatment with SGLT2 inhibitors was associated with a significantly greater decrease in weight change from baseline (weighted mean differences −2.01 kg, 95% confidence interval −2.18 to −1.83 kg, P < 0.001). Compared with a placebo, changes with GLP ‐1 treatment were also associated with a comparable decrease in weight change from baseline (weighted mean differences −1.59 kg, 95% confidence interval −1.86 to −1.32 kg, P < 0.001). Meta‐regression analysis showed that the baseline age, sex, baseline glycated hemoglobin, diabetes duration or baseline body mass index were not associated with the weight change from baseline in SGLT2 inhibitors or in GLP‐1 treatment corrected by placebo. Comparisons of weight changes from baseline corrected by placebo between SGLT2 inhibitors and GLP‐1 treatment showed that the difference was not significant ( P > 0.05). Conclusions: According to the present meta‐analysis, treatment with SGLT2 inhibitors and treatment with GLP‐1 analogs led to comparable weight changes from baseline, which are both with significance when compared with placebo treatment.